A phenomenological study of the lived experience of nurses in the battle of COVID-19 - Gunawan, Joko (Nurs Outlook, 2021)
BACKGROUND: Roles and responsibilities of nurses are crucial in the battle of Coronavirus disease 2019 (COVID-19), but nursing duties also put them at risk for infections. PURPOSE: The purpose of this study was to explore the lived experience of nurses in combatting COVID-19 in Belitung, Indonesia. METHODS: This study employed a phenomenological study design. Online interviews and chatting were conducted among 17 clinical nurses who were purposively selected from March to June 2020. Data were audio-recorded, transcribed, and validated among researchers. The thematic approach was used for data analysis. FINDINGS: Seven themes emerged (1) feeling “nano-nano”, (2) lack of N95 masks, (3) we are just pawns, (4) being rejected, (5) please do not spread our identity, (6) we miss home, and (7) feeling betrayed by regulation. DISCUSSION: Findings of this study should be used by government agencies, nurses, and the general population in combatting COVID-19.